Redução do retrabalho na implantação de sistemas de gestão empresarial - Souza, Michele de (Universidade do Vale do Rio dos Sinos, 2019)
Rework can imply costs and reduce developer profitability in enterprise management systems deployment projects. Reducing rework promotes greater adherence to project schedules and project costs by increasing the competitiveness of the system developers. Despite the potential benefits of rework mitigation, literature on the subject is scarce. This work investigated the inductors of rework on business systems implantation, their mitigation and management implications. The research used the method of multiple case study, qualitative and exploratory. The survey was conducted in small and medium-sized developers of enterprise management systems. The investigated companies have an average of 18 years of experience in the market with projects consolidated and praised by their clients. Project managers and implementation consultants with project experience were interviewed. The results contribute by indicating the inductors of rework and their mitigation. Rework inducers in enterprise management systems deployment projects include excessive commercial sector empowerment, poor developer empowerment, and disconnection of project specifications with customer demands, customer manager resilience, insecurity of the client's employees, the reactivity of the client's employees, the distancing of the professionals, the internal conflicts, the deficient training and the planning of the implantation. The mitigation of these inductors requires training, approaching designers and service professionals, managing conflicts, valuing users 'opinions, selecting users' profiles and managing project resources. Observing and applying these mitigators enables successful projects, as well as increased results and profitability for developers.
Keywords: Retrabalho; Mitigação do retrabalho; Implantação sistemas de gestão; Serviços; Rework.; Mitigation of rework; Deployment management systems; Services; ACCNPQ::Engenharias::Engenharia de Produção